2014
DOI: 10.1371/journal.pone.0096871
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Correlates of Motor Speed in the Cerebellar Anterior Lobe

Abstract: In athletics, motor performance is determined by different abilities such as technique, endurance, strength and speed. Based on animal studies, motor speed is thought to be encoded in the basal ganglia, sensorimotor cortex and the cerebellum. The question arises whether there is a unique structural feature in the human brain, which allows “power athletes” to perform a simple foot movement significantly faster than “endurance athletes”. We acquired structural and functional brain imaging data from 32 track-and-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
(68 reference statements)
1
18
0
1
Order By: Relevance
“…This population response drives the BOLD-signal which is picked up by fMRI (Logothetis, Pauls, Augath, Trinath, & Oeltermann, 2001) and therefore explains the insignificant speed-related M1 activation in our results. Likewise, Wenzel et al (2014) found no speed-specific BOLD-activation in M1 for fast versus slow plantar flexion of the ankle. Similar to our results, Turner et al (2003) did not find significant activation in M1 in a PET study that varied movement extent/speed.…”
Section: Brain Regions With Movement-related Activation Irrespectivmentioning
confidence: 83%
“…This population response drives the BOLD-signal which is picked up by fMRI (Logothetis, Pauls, Augath, Trinath, & Oeltermann, 2001) and therefore explains the insignificant speed-related M1 activation in our results. Likewise, Wenzel et al (2014) found no speed-specific BOLD-activation in M1 for fast versus slow plantar flexion of the ankle. Similar to our results, Turner et al (2003) did not find significant activation in M1 in a PET study that varied movement extent/speed.…”
Section: Brain Regions With Movement-related Activation Irrespectivmentioning
confidence: 83%
“…In this study, the greater cerebellum GMV was specifically located in the lobules IV-V of the cerebellum and the IV-V vermian lobules in the anterior cerebellum lobe. These areas represent the arms, hands, and feet (Buckner, Krienen, Castellanos, Diaz, & Yeo, 2011;Manni & Petrosini, 2004) and are especially involved in motor execution, synchronization, coordination, control, and prediction (Cerasa et al, 2017;Koziol et al, 2014;Stoodley & Schmahmann, 2010;Wenzel, Taubert, Ragert, Krug, & Villringer, 2014). In addition, the GMV expansion in the athlete group extended to the bilateral lingual gyrus, PCC, and PCUN, which played important roles in visual attention.…”
Section: Gmv Differences Between Athletes and Controlsmentioning
confidence: 99%
“…Third, movement speed (and not movement amplitude or directional-change), positively correlates with cerebellar activity in human imaging studies [Lewis et al, 2003;Turner et al, 1998;Wenzel et al, 2014]. Fourth, there is even evidence for perceptual sensitivity to speed in the cerebellum, as cerebellar patients show impairments in making perceptual judgments regarding the speed of moving visual stimuli but not their position [Ivry and Diener, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the average firing rate and modulation depth of cerebellar cells more frequently increases rather than decreases with faster speed [Roitman et al, ], a property which may be expected to be reflected in positive modulation of the fMRI signal. Third, movement speed (and not movement amplitude or directional‐change), positively correlates with cerebellar activity in human imaging studies [Lewis et al, ; Turner et al, ; Wenzel et al, ]. Fourth, there is even evidence for perceptual sensitivity to speed in the cerebellum, as cerebellar patients show impairments in making perceptual judgments regarding the speed of moving visual stimuli but not their position [Ivry and Diener, ].…”
Section: Discussionmentioning
confidence: 99%